Contribution of Self-esteem and Parents Social Support to Students Academic Resilience in Online Learning - Hidayatul Hasanah; Marjohan Marjohan; Daharnis Daharnis (International Journal of Applied Counseling and Social Sciences, 2020)
This research aims to analyze the contribution of self-esteem and social support of  parents together on the academic resilience of students in online learning. This research uses a descriptive correlational quantitative method. The research population was 304 students of SMA Negeri Agam Cendekia, with a sample of 173 students, who were selected using the proportional stratified random sampling technique. The instruments used were inventory self-esteem, parents social support scale, and academic resilience scale with a Likert model, that had met the validity and reliability requirements. The research data were analyzed using simple regression techniques and multiple regression. The results of this research indicate that: (1) on average selfesteem, parents social support and student academic resilience in online learning at SMA Negeri Agam Cendekia are in the medium category, (2) self-esteem contributes 43% to academic resilience in online learning . (3) parents social support contributed 56,8% to academic resilience in online learning . (4) self-esteem and parental social support together contribute 65% to academic resilience in online learning . The implications of the research results can be used as a basis in the preparation of guidance and counseling service programs at SMA Negeri Agam Cendekia.